High power density and improved H2 evolution reaction on MoO3/Activated carbon composite. (6th March 2020) - Sangeetha, D.N.; Holla, R. Sowmya; Ramachandra Bhat, Badekai; Selvakumar, M.
Abstract: The formation of hexagonal MoO3 (h- MoO3 ) microrods was favoured at lower pH in the hydrothermal synthesis method. Symmetric and Hybrid supercapacitors were fabricated using h-MoO3 /plastic bottle derived activated carbon (PAC) composite in 1 M Na2 SO4 aqueous electrolyte. The operating voltage for the aqueous electrolyte was maximized to 1.6 V with this combination. The wide operating voltage led to a maximum specific capacitance of 211 Fg -1, power density of 287 W kg −1 and 79% efficiency even at 5000 charge-discharge cycles for the hybrid supercapacitor combination. The combined effect of PAC micropores along with the 1-D rod-shaped h-MoO3, helped in faster charge-transfer, hence increasing the efficiency of supercapacitors. Further, the composites of defective PAC (PDAC) together with the h-MoO3 when tested for hydrogen evolution reactions (HER), provided lesser onset potential and Tafel slope values of −0.23 mV and −93 mVdec −1 . There was a change in the structural environment of carbon due to the heteroatom doping and dedoping producing defects in PAC, termed as PDAC. These defects together with the hexagonal microrods of MoO3 provided fast electron transfer towards hydrogen adsorption/desorption hence effectively producing H2 . Graphical abstract: Image 1 Highlights: Maximum operating voltage for supercapacitor study up to 1.6 V with 1 M Na2 SO4 . Hybrid supercapacitor with maximum power density of 287 WKg -1 . 79% efficiency retained after 5000 charge-discharge cycles for hybrid combination. PDAC/h-MoO3 catalyzed HER at much lower Tafel slope value −98 mVdec −1 . Faster electron transport due to PDAC defects together with hexagonal MoO3 microrods.